2018
DOI: 10.31031/rism.2018.04.000578
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Avulsion of the Proximal Rectus Femoris Tendon with Significant Defect: A Successful Surgical Management

Abstract: Background: Rupture of the proximal rectus femoris tendon has been well documented in the literature because of a bony avulsion of the anteroinferior iliac spine predominantly in the active adolescent population. Most of these ruptures are treated non-operatively with good functional outcomes. However, when conservative treatments fail, surgery is an option.Purpose: To describe a rare case of successful surgical management of a chronic ruptured proximal rectus femoris tendon. Results:The patient progressively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Although there is a paucity of literature reporting the postoperative outcomes after suture anchor repair using the suture-bridge technique, previous clinical studies have reported satisfactory postoperative results for both tenodesis and suture anchor repair techniques using the single row technique 1,4,7,13,15,18,[20][21][22][23] (Table 3). Kayani et al 15 compared the postoperative clinical outcomes of tenodesis and suture anchor repair techniques for PRF injuries in professional athletes and reported that the tenodesis group had a shorter time to return to play at previous competitive level and a lower recurrence rate than the suture anchor repair group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a paucity of literature reporting the postoperative outcomes after suture anchor repair using the suture-bridge technique, previous clinical studies have reported satisfactory postoperative results for both tenodesis and suture anchor repair techniques using the single row technique 1,4,7,13,15,18,[20][21][22][23] (Table 3). Kayani et al 15 compared the postoperative clinical outcomes of tenodesis and suture anchor repair techniques for PRF injuries in professional athletes and reported that the tenodesis group had a shorter time to return to play at previous competitive level and a lower recurrence rate than the suture anchor repair group.…”
Section: Discussionmentioning
confidence: 99%
“…17 As the prevalence of reported PRF injuries is low, PRF injuries are often overlooked and undertreated, leading to chronic injuries with sustained symptoms and additional time lost from sports for the athletes. 9,1,6 Traditionally, PRF injuries in high-level athletes have been treated nonoperatively, utilizing a combination of stretching, ice, manual therapies, and gradual strengthening, with multiple studies reporting favorable clinical outcomes. 5,6,19 However, nonoperative treatment is often unsuccessful in high-level athletes for the reasons of not restoring the native anatomy of the PRF and scarring of the tendon, resulting in the recurrence of symptoms, diminished strength, decreased function, sustained pain, and cramping.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Athletes generally maintain full passive hip range of motion 3,19 and are able to perform a straight leg raise with discomfort 2 . Quadriceps weakness is generally appreciated with resisted knee extension, especially in chronic cases 3,5,9,27 .…”
Section: Presentationmentioning
confidence: 99%
“…Because of the low prevalence of reported injuries to the proximal rectus femoris, to our knowledge, no current consensus exists guiding optimal management in high-level athletes 3,8 . Moreover, proximal avulsions and ruptures are often overlooked and undertreated, leading to chronic injuries and additional time lost from sport 3,5,9 . The purpose of this article is to provide a concise overview of the prevalence, the anatomy, the mechanisms of injury, the diagnostic workup, the treatment options, and the reported outcomes and complications that occur with treatment of proximal rectus femoris avulsion injuries and ruptures in high-level athletes.…”
mentioning
confidence: 99%